2013
DOI: 10.7750/biodiscovery.2013.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct target genes and effector processes appear to be critical for p53-activated responses to acute DNA damage versus p53-mediated tumour suppression

Abstract: The p53 tumour suppressor is the most frequently mutated gene in human cancer. This transcription factor can be activated by diverse cellular stresses, including DNA damage and oncogene activation. Through transcriptional induction of appropriate target genes, p53 can stimulate activity in a broad range of effector pathways, most notably cell cycle arrest, cellular senescence and apoptotic cell death. Insensitivity to cell death-inducing signals and deregulated proliferation are two key hallmarks of cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 189 publications
(273 reference statements)
0
8
0
Order By: Relevance
“…", "author" : [ { "dropping-particle" : "", "family" : "Haupt", "given" : "Susan", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Berger", "given" : "Michael", "non-droppingparticle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Goldberg", "given" : "Zehavit", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Haupt", "given" : "Ygal", "nondropping-particle" : "", "parse-names" : false, "suffix" : "" } ], "container-title" : "Journal of cell science", "id" : "ITEM-1", "issue" : "Pt 20", "issued" : { "date-parts" : [ [ "2003" ] ] }, "page" : "4077-85", "title" : "Apoptosis -the p53 network. ", "type" : "article-journal", "volume" : "116" }, "uris" : [ "http://www.mendeley.com/documents/?uuid=8ec1ee91-ede7-4fdd-8db0-00797104a582" ] } ], "mendeley" : { "formattedCitation" : "(31)", "plainTextFormattedCitation" : "(31)", "previouslyFormattedCitation" : "(31)" }, "properties" : { "noteIndex" : 0 }, "schema" : "https://github.com/citation-stylelanguage/schema/raw/master/csl-citation.json" }} It is presently understood that the p53-mediated acute response to DNA damage is only part of p53-mediated tumour suppression (46). p53 carries out 'baseline surveillance' of the integrity of the genome along with its acute-phase functions.…”
Section: A Intrinsic Mitochondrial Pathwaymentioning
confidence: 99%
“…", "author" : [ { "dropping-particle" : "", "family" : "Haupt", "given" : "Susan", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Berger", "given" : "Michael", "non-droppingparticle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Goldberg", "given" : "Zehavit", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" }, { "dropping-particle" : "", "family" : "Haupt", "given" : "Ygal", "nondropping-particle" : "", "parse-names" : false, "suffix" : "" } ], "container-title" : "Journal of cell science", "id" : "ITEM-1", "issue" : "Pt 20", "issued" : { "date-parts" : [ [ "2003" ] ] }, "page" : "4077-85", "title" : "Apoptosis -the p53 network. ", "type" : "article-journal", "volume" : "116" }, "uris" : [ "http://www.mendeley.com/documents/?uuid=8ec1ee91-ede7-4fdd-8db0-00797104a582" ] } ], "mendeley" : { "formattedCitation" : "(31)", "plainTextFormattedCitation" : "(31)", "previouslyFormattedCitation" : "(31)" }, "properties" : { "noteIndex" : 0 }, "schema" : "https://github.com/citation-stylelanguage/schema/raw/master/csl-citation.json" }} It is presently understood that the p53-mediated acute response to DNA damage is only part of p53-mediated tumour suppression (46). p53 carries out 'baseline surveillance' of the integrity of the genome along with its acute-phase functions.…”
Section: A Intrinsic Mitochondrial Pathwaymentioning
confidence: 99%
“…The p53 protein is a sequence-specific transcription factor that regulates the expression of many genes, including its own function (through MDM2, MDM4 ), cell cycle arrest and DNA repair ( CDKN1A [p21CIP1], CDK2, GADD45, TRIM22 ), senescence ( PML, PAI -1), apoptosis ( BAX, PUMA, NOXA , survivin), growth factors ( IGFBP -3, PTEN ), translation (Sestrin), autophagy (Sirtuin1), and innate immune receptors (TLRs) (Barsotti et al 2012; Hasty and Christy 2013; Kitagawa et al 2013; Klettner 2012; Purvis et al 2012; Suzuki et al 2009; Valente et al 2013; Valente and Strasser 2013; Vuong et al 2012). Activation of p53 can also directly initiate apoptosis via down regulation of anti-apoptotic BCL2 family proteins, including BCL2, BCLXL, and induction of mitochondrial outer membrane permeabilization.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was demonstrated that increased phosphorylated p53 levels compared with the control led to an increased production of ROS in a dose-dependent manner. Therefore, the activation of the p53 pathway may be in response to the ROS-induced DNA damage ( 32 ). p53 may downregulate the expression of antioxidant enzymes including SOD and GPx under physiological conditions when acutely stressed.…”
Section: Discussionmentioning
confidence: 99%